SUBSTANTIATION METHOD OF BUNKER PORT FOR THE SHIP DURNING THE VOYAGE - Щербина, Ольга Василівна; Дрожжин, Олексій Леонідович; Тихоніна, Ірина Ігорівна (Science-based technologies, 2019)
During the own ships or chartered fleet operating, the transport operator faces a two-sided task: on the one hand, to transport the cargo from the port of loading to the port of destination in a safety navigation way in full preservation of its quantitative and qualitative characteristics, and on the other, to constantly maintain the ship in a seaworthy condition. At the same time, the transportation efficiency for a carrier is determined by the cost of transportation indicator, to increase which the inclusion of a bunkering port in the vessel’s traffic pattern has been practiced recently. Thanks to this reception, it becomes possible to take on board a larger cargoes volume while maintaining the seaworthiness of the vessel. In addition, the difference in the cost of the fuel in different regions provides an opportunity to increase profits from transportation. Obviously, the need for refueling with a bunker in ports that lie on sections of the route arises at large sea crossings. The determination of the specific case of the bunkering port, which determines the overall pattern of the vessel’s movement, is solved by solving two major tasks: determining the ship loading capacity, taking into account the sailing conditions and justifying the scheme of the vessel’s movement when transporting cargo in the range. Thus, the purpose of this article is to develop a methodology for substantiating the operation of ships, with the possibility of bunkering along the route along the sea route, taking into account the nature of the cargo. To test this methodology, calculations were carried out using the example of a bulk carrier vessel ‘Zoya Kosmodemyanskaya’ (deadweight 49880 mt), for operation on the Odessa-Dalian range with the grain cargo, the specific loading volume of which is 1.2 m3/mt. Istanbul, Piraeus, Colombo, and Singapore are selected as eligible. The methodology, presented in the article takes into account the influence of external factors on the cargo’s volume, such as the characteristics of the navigation area, which in turn affect the size of the minimum freeboard required to ensure the safety navigation.